2019
DOI: 10.1111/nep.13523
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life following kidney and simultaneous pancreas kidney transplantation

Abstract: Introduction Kidney and simultaneous pancreas kidney (SPK) transplant recipients are younger and fitter than most other dialysis patients, but are also more vulnerable in areas of social, emotional and physical interaction. Few studies have tracked their post‐transplant health‐related quality of life (HRQoL). Aim To assess HRQoL following kidney and SPK transplantation, with comparison to dialysis patients, people with multiple co‐morbidities and general population data. Methods Patients completed the Kidney D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…The HRQoL of patients improved in both study groups after transplantation, which underlines the therapeutic success of SPKT, besides medical outcomes and objective clinical parameters. This is in line with most published studies showing a signi cant improvement in patient-reported general HRQoL after SPKT and better diabetes-speci c quality of life [4,[10][11][12][13].…”
Section: Post-transplant Hrqolsupporting
confidence: 91%
See 1 more Smart Citation
“…The HRQoL of patients improved in both study groups after transplantation, which underlines the therapeutic success of SPKT, besides medical outcomes and objective clinical parameters. This is in line with most published studies showing a signi cant improvement in patient-reported general HRQoL after SPKT and better diabetes-speci c quality of life [4,[10][11][12][13].…”
Section: Post-transplant Hrqolsupporting
confidence: 91%
“…In a study by Rajkumar et al, twelve months after transplantation (KTA or SPKT) most HRQoL scores (seven out of eight) were better for women than for men. Moreover, HRQoL scores of female recipients were not statistically different from the control group in the general population [12]. The authors postulated that differences in expectations and appreciation of improvements in health after transplantation, differences in social network and emotional support may provide an explanation for these ndings.…”
Section: Post-transplant Hrqolmentioning
confidence: 89%
“…HRQoL of patients improved in both study groups after transplantation, which underlines therapeutic success of SPKT, besides medical outcome and objective clinical parameters. This is in line with most published studies show a significant improvement in patient reported general HRQoL after SPKT and better diabetes specific quality of life [4,[10][11][12][13].…”
Section: Post-transplant Hrqolsupporting
confidence: 91%
“…HRQoL scores (7 out of 8) were better for women than for men. Moreover, HRQoL scores of female recipients were not statistically different from the control group in the general population [12]. They postulated that differences in expectation and appreciation of improvements in health after transplantation, differences of the social network and emotional support may be an explanation for these findings.…”
Section: Post-transplant Hrqolmentioning
confidence: 98%
See 1 more Smart Citation